Agricultural technologies for marginal and landless farmers: the case of hybrid rice cultivation in India - Varsha Khandker; Vasant P Gandhi (Agricultural Economics Research Review, 2023)
Hybrid rice technology was launched in India in 1994. We analyse the farm-level data and find that the benefits of hybrid rice—and, therefore, adoption—vary by region and farmer type. Adoption is higher among farmers with inadequate water for irrigation and small landholdings and who cultivate a small percentage of their landholding with rice. Marginal and landless farmers, most of whom are subsistence farmers, cultivate hybrid rice because it yields more and provides food security for their household. These results explain why hybrid rice is more prevalent in marginal conditions of states such as Uttar Pradesh, Chhattisgarh, Gujarat—than in fertilized, irrigated, and transplanted regions.